ACCURACY OF MATHEMATICAL CRITICAL THINKING SKILLS ASSESSMENT WITH A MODERN APPROACH: GENERALIZED PARTIAL CREDIT MODEL - Hanim, Muziyati; Mujahidawati, Mujahidawati; Falani, Ilham; Prasasty, Aliffia Teja; Nurhidayati, Rina (Jurnal Visipena, 2025)
Critical thinking skills mathematical critical thinking skills are essential to face the challenges of the 21st century. These skills in schools is still not optimal because it is not supported by valid and reliable instruments. Instruments that are valid and reliable. This study aims to measure mathematical critical thinking skills through the Generalized Partial Credit Model (GPCM) approach, to increase the accuracy of the assessment. The test instrument used is an indicator-based description test FRISCO (Focus, Reason, Inference, Situation, Clarity, and Overview). The quantitative research method with an experimental design was applied to seventh grade students in four public junior high schools, North Bahar District, Muaro Jambi. North Bahar, Muaro Jambi. Data analysis using GPCM with software PARSCALE 4.1 SOFTWARE. The p value of the fit test of 0.335 (> 0.05) indicates that the question fit the GPCM model. Student ability estimates ranged from -2.23 to 2.35, with the majority in the low ability category. Item parameters showed discrimination values of 0.855-1.534 and difficulty levels of -0.123 to 0.238, indicating good quality and balanced questions. Test information function showed that the instrument effectively measured students' abilities at various levels. These results prove that GPCM is appropriate for developing a valid, valid, and balanced mathematical critical thinking assessment instrument valid, accurate, and informative.